Effectiveness Of Military Diplomacy Towards Nationalism, National Security and Unity - Lamsal, Hiranya Lal (Unity Journal, 2022)
Military diplomacy in every country strengthens unity, nationalism and national security. It acts as a specific domain of diplomacy that emphasizes primarily on the pursuit of foreign policy interest of the state in the field of security and defence policy, whose actions are associated on the use of negotiations and other diplomatic instruments. Nepal, being a sovereign kingdom, the nation needs a stout military foundation. In this regard, in the field of nationalism, national unity and security, Nepal Army drives its loyalty, obedience, sacrifice and etiquette to maintain common and control in the nation. Considering this fact, this study examines military diplomacy directed to national interest through the perceptions of general people of Rupandehi district, Lumbini Province of Nepal. This study aims at exploring effectiveness of military diplomacy for the well being of the nation and their role to maintain patriotic feeling through national security and unity, and harmonious civil-military relations. To carry out this research, a set of questionnaires was prepared through Google Docs and circulated to general people through emails and messenger. Altogether, 116 participants were taken as population in this study. The snowball sampling technique was used with an online survey tool to collect data. The collected data was analyzed in terms of simple statistical method of percentages. This study found that the effectiveness of military diplomacy for an important security and foreign policy. The result displayed that military diplomacy provides opportunities, security and strength which boosts the national power. It enumerates the activity of military force of the ministry of defense of the nation which conducts a diplomatic scenario to the enforcement of its foreign policy that is of a non-combat nature. It also signifies that military diplomacy marches towards nationalism, which gravitates to build up the interest of obtaining and maintaining the state’s sovereignty. Therefore, it is an essential tool for foreign policy at strategic level that adds to raise the degree of nationalism, national security and unity in the state.